Visualizing Academic Library Data to Understand Use Patterns and Trends - Yadav, Akhilesh K. S.; Ahmed, Sagiruddin (Journal of Information and Knowledge, 2020)
The main purpose of the study is to explore the pattern and trends of library usage. This study is based on library circulation data. Many tools and applications have been used for the research and data visualization e.g. Tableau, Voyant Tools, MSExcel, Google Ngram Viewer etc. The data set of library transaction was collected from the KOHA (Open Source Library Automation Software) of Sir Dorabji Tata Memorial Library (SDTM Library) of Tata Institute of Social Sciences (TISS), Mumbai. The research has been undertaken with the raw transaction data from the 2014 to 2018 time period. The striking trend suggests that from the year 2015 the number of books checked-out is declining every year. From the research it is also found that on Mondays maximum number of library transactions takes place at TISS library. Text visualization reflects that TISS library holds books in major domains of social sciences.